Gene Polymorphisms in Chronic Periodontitis - Marja L. Laine; Bruno G. Loos; W. Crielaard (Hindawi Limited, 2010)
We aimed to conduct a review of the literature for gene polymorphisms associated with chronic periodontitis (CP) susceptibility. A comprehensive search of the literature in English was performed using the keywords: periodontitis, periodontal disease, combined with the words genes, mutation, or polymorphism. Candidate gene polymorphism studies with a case-control design and reported genotype frequencies in CP patients were searched and reviewed. There is growing evidence that polymorphisms in the IL1, IL6, IL10, vitamin D receptor, and CD14 genes may be associated with CP in certain populations. However, carriage rates of the rare (𝑅)-allele of any polymorphism varied considerably among studies and most of the studies appeared under-powered and did not correct for other risk factors. Larger cohorts, well-defined phenotypes, control for other risk factors, and analysis of multiple genes and polymorphisms within the same pathway are needed to get a more comprehensive insight into the contribution of gene polymorphisms in CP.